Educação jurídica e direitos humanos: o caso do curso de Direito com os assentados da reforma agrária - Barros, Joseane Batista Azevedo (2015)
This research examines the concept of legal education with the settlers from the experiences of undergraduate programs in right- Class Special to the beneficiaries of the agrarian reform offered by the Federal University of Goiás (UFG) and the State University of Feira de Santana (UEFS). A legal education is in the context of the statement of higher education as a human right and the questioning of educational public policies on land reform context. Given this educational model as affirmative action, there is a partnership between universities, social movements and the National Institute of Colonization and Agrarian Reform (Incra), according to the guidelines of Decree No. 7352 of 2010, which established the Program National Education in Agrarian Reform (Pronera). The research discusses the concept of education as communication, autonomy and awareness in Freire's perspective, addressing the educational and legal basis of the legal concept of education with the settlers. Inserting the object of study in the field of human rights, research enjoys the realization of the right to higher education as a public good and a human right under construction, according to the approach advocated by Herrera Flores (2009). It starts from the assumption that the right to higher education is a legal instrument in the struggle for ownership of rights denied and neglected. The methodology of this work is based on the concept of Freire's popular education, relating it to the experience of legal education with the settlers. This theory deals with the political and emancipatory character of education. Thus, we analyze the legal discourse present in Civil Action No. Pubic 2008.35.00.013973-0 / GO and judicial sentence befitting the discussion on the legality and constitutionality of that course in UFG. The research corpus is made up of documents pertaining to public policies of higher education with the settlers, as well as the implementation of projects of the abovementioned legal courses. A review of documents indicates the tensions present in the creation process of the courses, focusing on the issue of affirmative action and the audience concerning the Pronera.